A STUDY TO REVIEW THE APPROPRIATENESS OF DRUG DOSAGE IN RENALLY IMPAIRED PATIENT BY IDENTIFYING, ANALYSING AND ADJUSTING DOSAGES IN A TERTIARY CARE TEACHING HOSPITAL - M, Rathod Mrudangsinh; Achankunju, Ancy; John, Rose Maria; Sam, Gloria K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives To identify and analyze drug dosing in renally impaired patient in a tertiary care teaching hospital and to categorize patients on the basis of gender, age, GFR (Glomerular Filtration Rate) and anemia. Methodology A prospective interventional study was conducted on the drug dosage in renally impaired patient by identifying, analyzing, and adjusting. Ethical clearance was obtained from the IEC (Institutional Ethical Committee). The study was conducted on 103 patients with renal impairment for a period of six months. During ward rounds, cases were collected and collected data were assessed and analysed by using Micromedex, Lexicomp. For the possible interventions, the dosage errors were reported along with the evidence. Results Out of the 103 patients, 73 were males and 30 were females and majority of patients belonged to the age group between 41- 65 yrs. 56.31% and 43.69% of patients were in the category B and category C of GFR respectively. A total of 244 co-morbidities were present in 103 patients with HTN (Hypertension) and Type 2 DM (Diabetes Mellitus) the foremost. In total, 983 drugs were prescribed to the total patient with an average of 9.54 drugs per patient, 175 drugs required dosage adjustment. Conclusion The present study effectively reports all the interventions to the physicians along with the supporting data. Continuous medical education to the physicians together with pharmacists may reduce the chances of incongruity in drugs given to the renally impaired patients. Key Words: Renal impairment, MDRD (Modification of Diet in Renal Disease), Creatinine Clearance, Dosage Adjustment